Engineering tasks for BFT quality assurance - Roca J.; Roca J.J.; Soto F.; Villarejo J.A.; Mateo A. (Domestication of the bluefin tuna Thunnus thynnus thynnus, 2003)
Due to the spread of bluefin tuna farms and processing plants, automation (among many other engineering techniques) may help in the development of effective quality assurance methods. This paper seeks to display the technological resources available, as part of an ideal system conceived to achieve this goal from a global standpoint.
1. International Symposium on Domestication of the Bluefin Tuna Thunnus Thynnus Thynnus, 2002/02/03-08, Cartagena (Spain)